Hubungan Antara Transparansi Anggaran dan Partisipasi Publik Dalam Green Budgeting Pemerintah Pusat - Fathia, Syaharani Noer (BADAN PENERBIT STIEPARI PRESS, 2025)
This study examines the relationship between budget transparency and public participation in the implementation of Green Budgeting by the central government. The background of the research is based on the importance of fiscal transparency and public involvement in supporting budget policies oriented toward environmental sustainability. The objective of this study is to analyze the extent to which these two factors influence the effectiveness of Green Budgeting implementation. A quantitative approach was employed using a survey method involving 55 respondents from the general public, applying a Likert scale to measure perceptions of the studied variables. The data were analyzed using linear regression to determine the relationship between budget transparency (X1), public participation (X2), and Green Budgeting (Y). The results indicate that both budget transparency and public participation significantly influence the implementation of Green Budgeting, The regression coefficient for budget transparency was higher than that of public participation, indicating that information openness has a stronger influence in promoting the success of environmentally focused budget policies. The study concludes that enhancing transparency and public participation is crucial for strengthening the management of government budgets aimed at sustainability, and both elements must be consistently integrated into the fiscal policy framework of the central government.